Quality of Physics Teaching Module Based on Problem-Based Learning Model Integrated with PhET Simulation on Energy and Its Transformation - Muhammad Yusuf; Raghel Yunginger; Riris Nainggolan (Jurnal Penelitian Pendidikan IPA, 2024)
The present work seeks to develop physics learning tools by integrating PhET simulations with problem-based learning models on energy and its transformation on Vocational High School in class X of SMK Negeri 1 Sentani. It applied the 4D model, consisting of the define, design, develop, and disseminate stages. The developed teaching modules have met the quality criteria of the learning material analyzed based on aspects of validity, practicality, and effectiveness. Based on validity, approximately 85% of the designed learning tools are categorized as Very Valid. Based on practicality, the learning implementation can be effectively applied 87.48%, and students responded very positively with a weight of 4. Meanwhile, students were actively involved based on effectiveness, with approximately 84.24% active participation. Furthermore, based on student learning outcomes, it indicated that 97% of students completed, with only 2 out of 32 students failing. Student learning outcomes tend to be higher in the cognitive domains of C4 (analysis) and C5 (evaluation) compared to C3 (application) and C6 (creation). This research resulted in the suitable learning tools for class X students at SMK Negeri 1 Sentani.